Aprendizagem musical coletiva no projeto violões do mar com estudantes do 8o ano fundamental na ETIM Coronel Libório Gomes da Silva em Camocim-CE - Melo, Marcos Levi Bento (2023)
This dissertation has a qualitative approach, uses action-research whose objective is to analyze the process of musical learning through the collective practice of guitar in the Violões do Mar Project at Escola em Tempo Integral Municipal Coronel Libório Gomes da Silva in Camocim, Ceará. In addition, it problematizes changes necessary for the continuity of the elective discipline of Music Education in that school. The research subjects were 27 students of the 8th Elementary Year of the aforementioned school, aged between 13 and 15 years old. The research dialogues with Edwin E. Gordon's principles of music learning by discrimination (2015) and Keith Swanwick's C(L)A(S)P model of music education (1979). In this way, it recognizes the development and psychomotor learning in Jean Piaget (1987) and in some principles of active methods of musical education of the 20th century as guiding threads for the practice of collective musical learning of guitar in elementary school. The research results attest to the constructivist educational paradigm of designing education from learning; therefore, it suggests changing the traditional teaching model centered on the teacher towards collective musical learning, built by the students. From the analysis of documentary data and practices of collective musical learning in Projeto Violões do Mar, we identified that: a) students learn the guitar by listening, playing and singing in interaction with others; b) the musicalization process awakened the students' sound sensitivity to musical elements; c) encouraging performance was an important step in the formation of the musical educational process of the project's students; d) it is necessary to build other musical knowledge from the students' repertoire. Transdisciplinary, we found that the effect of collective musical action, through learning in the Project Violões do Mar, mediated aesthetic and artistic knowledge of the students of that school. We suggest that, for the continuation of the Music Education subject in the aforementioned school, it is necessary to understand music as scientific and artistic knowledge, thus building the musical pedagogical proposal in dialogue with the subject teacher, taking into account their attributions, workload, infrastructure adequate school for teaching music and working on projects. Music as a school disciplinary knowledge greatly contributes to the social, ethical and citizenship transformation of its students.